Respuesta :
Answer:
Hi there!
Your answer is:
x= -2
Step-by-step explanation:
-6x = 5x +22
Subtract 5x from both sides
-6x-5x = 22
Simplify
-11x = 22
Divide both sides by -11
x= 22/-11
Simplify
x= -2
Hope this helps!
Answer:
x=-2
Step-by-step explanation:
The equation here is -6x=5x+22
First we can move the term 5x to the left side by subtracting 5x from both sides of the equation giving us
-11x=22
From here we need to divide both sides of the equation by -11 to isolate the variable so we get
-11x/-11=22/-11
This then is simplified to
x=-2
Which is the answer.